RELEVANSI TRADISI PETIK LAUT MADURA TERHADAP ISU LINGKUNGAN GLOBAL DALAM MENDUKUNG SUMBER PEMBELAJARAN KONTEKSTUAL UNTUK SISWA SEKOLAH DASAR - Hanum Eka Pratiwi , Citra; Tri Febrianto, Priyono; Hoiris Zuhro, Istihana; Maghfirli Islami, Sabrina; Alya Agustina, Dea; Elsa Safila, Amanda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Environmental sustainability and the preservation of local culture have become important concerns in 21st-century education. The Petik Laut Madura tradition (Rokat Tase’) represents a form of local wisdom of coastal communities that reflects a harmonious relationship between humans and the marine environment. This study aims to analyze the relevance of this tradition to global environmental issues and its potential to support sustainability values as well as serve as a contextual learning resource in elementary education. This research employs a qualitative approach using a library research design by analyzing literature published between 2020 and 2026. The findings indicate that Rokat Tase’ embodies religious, social, cultural, and ecological values that promote environmental preservation. Furthermore, this tradition has the potential to enhance students’ understanding of social concepts, foster environmental awareness, and strengthen character development through social studies learning based on local wisdom.